2010
DOI: 10.1016/j.bmc.2009.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Isosorbide-based cholinesterase inhibitors; replacement of 5-ester groups leading to increased stability

Abstract: Isosorbide-2-carbamate-5-esters are highly potent and selective butyrylcholinesterase inhibitors with potential utility in the treatment of Alzheimer's Disease (AD). They are stable in human plasma but in mouse plasma they undergo hydrolysis at the 5-ester group potentially attenuating in vivo potency. In this paper we explore the role of the 5-position in modulating potency. The focus of the study was to increase metabolic stability while preserving potency and selectivity. Dicarbamates and 5-keto derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The release of isoidide was performed by aqueous hydrolysis of the acetates (no detailed experimental part, no yield given). 83 Scheme 12 Synthesis of isoidide through activation/SN2 reaction 83…”
Section: Laboratory Scale Synthesis Of Isoididementioning
confidence: 99%
“…The release of isoidide was performed by aqueous hydrolysis of the acetates (no detailed experimental part, no yield given). 83 Scheme 12 Synthesis of isoidide through activation/SN2 reaction 83…”
Section: Laboratory Scale Synthesis Of Isoididementioning
confidence: 99%
“…In the same way, isosorbide 1 can be regioselectively monoacetylated at the endo position using acetic anhydride in the presence of catalytic amount of lead(II) oxide to afford 5b in high yield [27]. Conversion to the corresponding glycals 4a [7,28] and 4b [3,4] was achieved by a two-step process: preliminary conversion to their triflate derivatives followed by in situ elimination of the triflate moiety with 1,8diazabicyclo [5.4.0]undec-7-ene (DBU) [29]. It is noteworthy to mention that glycals 4a,b are stable under neutral conditions and could be purified by flash chromatography.…”
Section: Scheme 1 Retrosynthetic Analysismentioning
confidence: 99%
“…Isosorbide-2-alkyl and aryl carbamates are selective and potent inhibitors of BuChE (e.g., 1 in Figure 1, IC 50 BuChE 4.3 nM), and they are selective for BuChE over AChE and related carboxylesterases including CE1 and CE2 found in human liver and intestine [22]. Whereas the 2-carbamate is essential to activity, we showed that the 5-position of the isosorbide scaffold could be modified in diverse ways producing more or less potent compounds [23]. We hypothesised that it might be possible to retain the inhibitory isosorbide-2-carbamate functionality but substitute the effective 5-benzoate in 1 with lipoic acid or ferulic acid esters, retaining cholinesterase sub-type selectivity while introducing new disease modifying functionality as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%